Post-Ablation Cavity Evaluation: A Prospective Multicenter Observational Clinical Study to Evaluate Hysteroscopic Access to the Uterine Cavity 4 Years after Water Vapor Endometrial Ablation for the Treatment of Heavy Menstrual Bleeding - Johns, D. Alan; Garza Leal, José Gerardo; Diamond, Michael P.; Harris, Micah (2020)
Study Objective: Patients who have undergone endometrial ablation may present a diagnostic challenge when they subsequently develop vaginal bleeding, pelvic pain, or postmenopausal bleeding. Extensive scarring of the uterine cavity often precludes evaluation and/or conservative treatment. For further research on this topic, we performed hysteroscopic examination in study subjects a mean duration of 4 years after they had undergone water vapor endometrial ablation. Design: Prospective, multicenter, observational clinical study. Setting: Eight private practice or outpatient sites in the United States and Mexico. Patients: Seventy subjects who had completed their 36-month follow-up in the AEGEA Pivotal Trial. Interventions: Diagnostic hysteroscopy. Measurements and Main Results: The subjects were screened for general health and infection and underwent diagnostic hysteroscopy. Menstrual bleeding status was recorded. The video of the hysteroscopic examination was analyzed by an independent reviewer, who assessed uterine cavity access and visualization of the cornua and tubal ostia as well as characterized adhesions on the basis of the criteria by March et al. An independent reviewer also subjectively assessed whether Pipelle endometrial biopsy or intrauterine device placement would be feasible. Uterine cavity access was achieved in 90% (63/70) of subjects. Among subjects with cavity access, the cornua and ostia were visualized in 79% (50/63) and adhesions were absent in 75% (47/63), with only 2 women having severe adhesions (3%, 2/63). Biopsy was projected to be feasible in 86% (62/70) and intrauterine device placement in 60% (42/70) of all subjects. The subjects’ bleeding statuses were not correlated with uterine cavity access. The results were consistent for subjects with large uterine cavities and International Federation of Gynecologic and Obstetrics type II to VI myomas ≤4 cm. Conclusion: Water vapor endometrial ablation preserved an accessible uterine cavity and visualization of the ostia in most subjects, with minimal incidence of severe adhesions, a mean of 4 years after the ablation procedure.